The effects of Qingchang Ligan formula on hepatic encephalopathy in mouse model: results from gut microbiome-metabolomics analysis - Yang, Ziwei; Liu, Shuhui (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundHepatic encephalopathy (HE) is a neurological disorder resulting from advanced liver injury. HE has a high mortality rate and poor prognosis. The pathogenesis of HE is still unclear, which has led to the lack of a satisfactory specific treatment method. There is increasing evidence that the intestinal flora affects the communication between the gut and the brain in the pathogenesis of HE. Adjusting the intestinal flora has had a beneficial effect on HE in recent studies, and the Qingchang Ligan formula (QCLG) has been shown in previous studies to regulate intestinal flora and metabolites. In this study, we established a thioacetamide-induced HE mouse model to evaluate the protective effect of QCLG on HE and explore its potential mechanism, which also demonstrated that intestinal flora dysbiosis is involved in the pathogenesis of HE.MethodsMice were intraperitoneally injected with thioacetamide (TAA, 150 mg/kg) to induce HE. Additionally, they were orally administered Qingchang Ligan Formula (QCLG) at a dose of 6.725 g/kg·d for seven days, while control mice received an equal volume of saline via gavage. Subsequently, samples were subjected to 16S ribosomal ribonucleic acid (rRNA) gene sequencing, high-performance liquid chromatography-mass spectrometry (LC-MS), and RNA-sequencing (RNA-seq) analysis.ResultQCLG improved weight loss, cognitive impairment, neurological function scores, blood ammonia, and brain gene expression of interleukin-6 (TNF-α), Interleukin-1β (IL-1β), and interleukin-6 (IL-6) induced by HE. Moreover, QCLG increased the levels of liver function indicators, including alanine aminotransferase (ALT), aspartate aminotransferase (AST), and serum TNF-α, IL-1β, and IL-6. 16S RNA sequencing revealed increased Oscillibacter, Colidextribacter, and Helicobacter in TAA-induced mouse fecal samples. Also, the abundance of Bifidobacterium decreases TAA-induced mouse fecal samples. In contrast, QCLG treatment significantly restored the gut microbial community. Metabolomics indicated significant differences in some metabolites among the normal control, treatment, and model groups, including 5-methoxytryptophan, Daidzein, Stercobilin, and Plumieride (PLU).ConclusionQCLG can alleviate neuroinflammation and prevent HE caused by liver injury by regulating intestinal flora in mouse models.